Health care for cases of cutaneous leishmaniasis at an emergency care unit in the médio-Araguaia region (Research, Society and Development, 2024)
The present study aimed to analyze the care provided to International Classification of Diseases (ICD) for leishmaniasis and to outline the sociodemographic profile of patients attended to at the UPA in 2019 in the Médio-Araguaia region. This is a documentar study type with a quantitative and retrospective approach conducted through the analysis of medical records of patients attended to at the Emergency Care Unit of Barra do Garças municipality - Mato Grosso, during 2019 with leishmaniasis ICDs (B550 - visceral leishmaniasis/ B551 - cutaneous leishmaniasis/ B552 - mucocutaneous leishmaniasis/ B559 - unspecified leishmaniasis). Through the analysis of electronic medical records, it was possible to identify that 985 treatments were provided during 2019 with leishmaniasis ICDs or those who used medication for leishmaniasis. The study demonstrates that the vast majority of cases attended with leishmaniasis ICDs were cutaneous with 463 treatments. Socio-demographic profile results reveal that the highest prevalence of American Tegumentary Leishmaniasis occurred in males (67.79%), non-indigenous individuals (96.61%), and in the age group of 12 to 49 years old (48.30%). It is concluded by noting the need to strengthen public health with individual and collective actions aimed at guiding users regarding different levels of healthcare attention and promoting ongoing education for medical professionals and nurses, with the aim of ensuring correct completion of medical records.